Role of nuclear factor-κB (NFκB) in microglial polarization in correlation with neuroinflammatory mechanism at the hippocampal cornu ammonis (CA) 1 region after acute and chronic phase of global ischemic brain injury in rats - Wibisono, Dian Prasetyo; Nur Arfian; Fauziyatul Munawaroh; Dwi Cahyani Ratna Sari (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
Ischemic brain injuries can result in hippocampal injury due to its vulnerability to ischemia, specifically the CA1 region. Ischemic injury to this region alters nerve cells, synapses, and non-neural hippocampal tissue and causes hippocampal sclerosis. This injury could be mediated by microglia via the neuroinflammation pathway. However, the neuroinflammatory mechanism underlying hippocampal ischemic injury is still unclear. This study aimed to investigate the role of NF-κB in microglia polarization which affects the hippocampal area after ischemic injury. We conducted a quasi-experimental study, using 24 male Sprague Dawley rats aged 4 wk old and weighing 100 g. The rats were grouped into 4 different groups (CL1 as acute, CL3 as subacute, CL7 as chronic, and SO as control groups) and performed bilateral common carotid artery ligation to induce global ischemic injury in the brain. The difference in microglial activation was tested using immunohistochemistry for CD68. Moreover, polymerase chain reaction (PCR) was utilized to assess mRNA expression differences in IL1β, IL6, TNFα, and NF-κB. An increase in the number of positive CD68 fraction areas in CL1, CL3, and CL7 compared to the SO group (p=0.002) was shown after bilateral common carotid artery ligation. Such ligation also induced a significantly higher mRNA expression of IL1β (p=0.004), IL6 (p=0.028), TNFα (p=0.028), and NF-κB (p=0.002) in the CL1, CL3, and CL7 groups, compared to the SO group. In conclusion, NF-κB is the key player in hippocampal injury in the CA1 region following ischemic event by differentiating microglia into M1 phenotype form and initiates the neuroinflammatory cascade via IL1β, IL6, and TNFα in all phases.